Pengembangan Website Paud Terpadu Aisyiyah Kaliwates Jember Menggunakan Blogger dan Bootstrap - Rhomdani, Rohmad Wahid; Rahayu, Lusiana Dewi (Universitas Respati Indonesia, 2022)
Website development research methods Paud Terpadu Aisyiyah Kaliwates his is using the Waterfall model. The development of the Aisyiyah Paud Terpadu website has been successfully built and used for school promotion and can be used to convey school profile information. This website is in accordance with the current 4.0 technological developments and is very much needed for accuracy and speed and convenience for various parties. From what researchers have done, creating a website using blogger and bootstrap is very suitable because the responsive bootstrap technology is used both on the android & desktop.Keywords: Website, blogger and bootstrap